The Shift from Pen-and-Paper to Computer-Based Testing in Waec and Jamb on The Academic Performance of Senior Secondary School Students in Ozuzu Clan, Rivers State - Chigbu Prince Ozioma (International Journal on Integrated Education, 2026)
The article discussed the change in pen-and-paper to computer-based testing in WAEC and JAMB on the academic performance of Senior Secondary School Students in Ozuzu Clan, Rivers State. The research was informed by four objectives, four research questions and four hypotheses. The research design used in this study is a mixed-methods research design, which combines both quantitative and qualitative research. The research was carried out in Ozuzu Clan, Etche in Rivers State, Nigeria. The study population will be senior secondary school students in Ozuzu Clan, Etche in Rivers State. The local education authority estimates that there are about 6,000 senior secondary school students in the areaA sample size of 600 students was chosen in this study. This sample size is considered adequate to give reliable and valid results and also to be subject to statistical analysis. The sampling method used in the study was a stratified random sampling. A combination of semi-structured interviews and structured questionnaires was used to collect data. The questionnaires were analyzed with the help of Descriptive statistics (mean, median, mode, standard deviation) to summarize the data, and the inferential statistics (t-tests, ANOVA) will be applied to identify the significance of the differences in academic performance between students who have undergone CBT and those who have not. According to the findings, the following conclusion and recommendations were drawn The introduction of computer-based testing (CBT) in the West African Examinations Council (WAEC) and the Joint Admissions and Matriculation Board (JAMB) has brought a major change in the assessment environment of senior secondary school students in the Ozuzu Clan, Rivers State. The research finds that although there was resistance and technological obstacles at the beginning, the overall effects of CBT on the academic performance of students have been mostly positive. Students who adjusted to the new system showed better performance, which means that the introduction of technology in education can lead to better learning results. Schools ought to introduce extensive training to students and teachers to introduce them to CBT platforms. This will assist in alleviating the initial difficulties and enhance the overall performance and The government and educational authorities ought to invest in the required infrastructure, such as the availability of reliable internet and computer facilities, so that all students have equal chances to engage in CBT.